Compression of Multilayered Composite Electrospun Scaffolds: A Novel Strategy to Rapidly Enhance Mechanical Properties and Three Dimensionality of Bone Scaffolds. (13th January 2013) - Madurantakam, Parthasarathy A.; Rodriguez, Isaac A.; Garg, Koyal; McCool, Jennifer M.; Moon, Peter C.; Bowlin, Gary L.
Abstract : One major limitation of electrospun scaffolds intended for bone tissue engineering is their inferior mechanical properties. The present study introduces a novel strategy to engineer stiffer scaffolds by stacking multiple layers and cold welding them under high pressure. Electrospun polydioxanone (PDO) and PDO:nanohydroxyapatite (PDO:nHA) scaffolds (1, 2, or 4 layered stacks) were compressed either before or after mineralizing treatment with simulated body fluid (SBF). After two weeks in SBF, scaffolds were analyzed for total mineral content and stiffness by Alizarin red S and uniaxial tensile testing, respectively. Scaffolds were also analyzed for permeability, pore size, and fiber diameter. Results indicated that compression of multiple layers significantly increased the stiffness of scaffolds while reducing mineralization and permeability. This phenomenon was attributed to increased density of fibers and loss of surface area due to fiber welding. Statistics revealed, the 4-layered PDO:nHA scaffold compressed first followed by mineralization in revised SBF had maximal stiffness, low permeability and pore size, and mineralization second only to noncompressed scaffolds. Within the limitations of permeability and pore size, this scaffold configuration represents an optimal midway for desired stiffness and mineral content for bone tissue engineering.